The End of the Cold War? - Plato, Alexander von. author. aut Link
XV, 439 p.
Keywords: This carefully researched history draws on archival sources as well as a wealth of new interviews with on-the-ground activists, political actors, international figures, and others to move beyond the narratives both the German and American varieties that have dominated the historical memory of German reunification.